EXTH-92. TARGETING PRIMARY CENTRAL NERVOUS SYSTEM B CELL LYMPHOMA IGH CLONOTYPES USING NOVEL RNA-NPS. (14th November 2022) - Ogando-Rivas, Elizabeth; Von Roemeling, Christina; Castillo, Paul; Liu, Ruixuan; Mendez-Gomez, Hector; Thomas, Nagheme; Weidert, Frances; Chardon-Robles, Jonathan; Qdaisat, Sadeem; Cascio, Matthew; Ligon, John; Huang, Jianping; et al.
Abstract: BACKGROUND: Recurrent PCNSBLs represent a therapeutic challenge. Up to 60% of PCNSBL patients relapse to later face survival rates as low as 22%. Unfortunately, tumor heterogeneity and off-target effects have limited the success of immunotherapy against PCNSBL. METHODS: We propose a novel immunotherapy to overcome PCNSBL heterogeneity and off-target effects in an exquisitely tumor specific manner using nanoparticle vaccination, capable of delivering personalized tumor derived mRNAs, that induces systemic orchestration of innate and adaptive immunity. We target tumor antigens derived from the B cell receptor (i.e., heavy chain immunoglobulin - IgH) clonotypes. IgH clonotypes are hypervariable gene rearrangements clonally generated by B cells. Tumor IgH clonotypes are unique for each malignant B cell clone and hence attractive immune targets, not shared by normal B cell clones avoiding undesirable off-target effects. RESULTS: RNA-NPs can reprogram tumor microenvironment while activating the innate immunity via IFN type I (i.e., IFNα) and priming of hypervariable region clonotype specific T cell responses in naïve mice. We determined the rearranged IgH sequences (predominant clone 99% and nine additional clones with frequencies < 1%) of clinically relevant inbred murine PCNSBL models (BAL17 and A20) by PCR. The number of identified clonotypes confirmed the IgH variability observed in human B cell hematological malignancies. In preliminary experiments targeting lymphoma derived single clonotypes with RNA-NPs, we showed the feasibility of priming in-vivo T cells specific against hypervariable regions after 3 weekly i.v. RNA-NPs (median IFNγ: 58 pg/ml; range: 50-70 pg/ml vs controls < 30 pg/ml; p=0.008). Targeting of clonotype RNA-NPs was associated with decreased tumor growth (p=0.04). Interestingly, we have observed tumor reactive lymphangiogenesis that communicates with regional skull bone marrow observed in 3D microscopy that might direct future routes of RNA-NP administration. CONCLUSION: Our RNA-NP systemic vaccination platform can induce PCNSBL clonotype specific T cell responses, sparing normal tissues.